PERAN FASILITATOR PUSPAGA DALAM PENCEGAHAN KEKERASAN (BULLYING) MELALUI SOSIALISASI EDUKASI "PUSPAGA GOES TO SCHOOL" - Oktarizka Reviandani; Putri Amalia Zahroh (Journal Publicuho, 2024)
This study aims to describe how the role of PUSPAGA facilitators in the implementation of the 'PUSPAGA goes to school' educational socialization program. In this PUSPAGA activity, it provides services handled by professionals such as counseling, outreach, parenting classes and several child abuse prevention measures. This research was written using descriptive qualitative research methods. The data collection techniques used in this research are observation, documentation and library research. This research uses a type of qualitative research with the subjects of several junior high schools in the Krembangan sub- district of Surabaya city. The results of this study indicate that acts of violence are still widely carried out in the school environment, the perpetrators of bullying are common at the junior high school level. The acts of bullying that occur are verbal bullying and physical bullying. In this study also describes what the role of the puspaga facilitator is in addition to providing material, it also acts as a) a PUSPAGA facilitator as an inspirator, b) a PUSPAGA facilitator as an informator, c) a PUSPAGA facilitator as an organizer, d) a PUSPAGA facilitator as a motivator, g) a PUSPAGA facilitator as an initiator, and g) a PUSPAGA facilitator as a mediator. In addition, the researcher also explained what a puspaga is and stated that puspaga runs under DP3AAPKB.